1,2-Dithiole-3-Ones as Potent Inhibitors of the Bacterial 3-Ketoacyl Acyl Carrier Protein Synthase III (FabH) - He, Xin (American Society for Microbiology, 2004)
The enzyme FabH catalyzes the initial step of fatty acid biosynthesis via a type II dissociated fatty acid synthase. The pivotal role of this essential enzyme, combined with its unique structural features and ubiquitous occurrence in bacteria, has made it an attractive new target for the development of antibacterial and antiparasitic compounds. We have searched the National Cancer Institute database for compounds bearing structural similarities to thiolactomycin, a natural product which exhibits a weak activity against FabH. This search has yielded several substituted 1,2-dithiole-3-ones that are potent inhibitors of FabH from both Escherichia coli (ecFabH) and Staphylococcus aureus (saFabH). The most potent inhibitor was 4,5-dichloro-1,2-dithiole-3-one, which had 50% inhibitory concentration (IC(50)) values of 2 μM (ecFabH) and 0.16 μM (saFabH). The corresponding 3-thione analog exhibited comparable activities. Analogs in which the 4-chloro substituent was replaced with a phenyl group were also potent inhibitors, albeit somewhat less effectively (IC(50) values of 5.7 and 0.98 μM for ecFabH and saFabH, respectively). All of the 5-chlorinated inhibitors were most effective when they were preincubated with FabH in the absence of substrates. The resulting enzyme-inhibitor complex did not readily regain activity after excess inhibitor was removed, suggesting that a slow dissociation occurs. In stark contrast, a series of inhibitors in which the 5-chloro substituent was replaced with the isosteric and isoelectronic trifluoromethyl group were poorer inhibitors (IC(50) values typically ranging from 25 to >100 μM for both ecFabH and saFabH), did not require a preincubation period for maximal activity, and generated an enzyme-inhibitor complex which readily dissociated. Possible modes of binding of 5-chloro-1,2-dithiole-3-ones and 5-chloro-1,2-dithiole-3-thiones with FabH which account for the role of the 5-chloro substituent were considered.